2010
DOI: 10.1158/0008-5472.can-10-2288
|View full text |Cite|
|
Sign up to set email alerts
|

Peptide Vaccination after T-Cell Transfer Causes Massive Clonal Expansion, Tumor Eradication, and Manageable Cytokine Storm

Abstract: Adoptive T-cell transfer (ACT) is successfully applied as a cancer treatment that is based on the activation and effector functions of tumor-specific T cells. Here, we present results from a mouse model in which ACT is combined with a long peptide-based vaccine comprising gp100 T-cell epitopes. Transferred CD8 + T cells expanded up to 1,000-fold after peptide vaccination, leading to a 3-fold increase in white blood cell count and a very high frequency in the generation of antigen-specific memory T cells, the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…27 Such activation leads to increased expansion or proliferation of CD4 + or CD8 + T cells 29 accompanied by IFNG production, 27 processes that have been found to be important for antitumor immunity, ICD and tumor immunogenicity. 11,13,29,30 Interestingly it was recently reported that in the case of chemotherapy-induced ICD, blockage of autophagy can cause ablation of CD4 + or CD8 + T cell immunity. 13 In case of Hyp-PDT induced ICD instead, autophagy attenuation in cancer cells caused superior stimulation of T cells, leading to a significantly increased expansion of the CD4 + or CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Such activation leads to increased expansion or proliferation of CD4 + or CD8 + T cells 29 accompanied by IFNG production, 27 processes that have been found to be important for antitumor immunity, ICD and tumor immunogenicity. 11,13,29,30 Interestingly it was recently reported that in the case of chemotherapy-induced ICD, blockage of autophagy can cause ablation of CD4 + or CD8 + T cell immunity. 13 In case of Hyp-PDT induced ICD instead, autophagy attenuation in cancer cells caused superior stimulation of T cells, leading to a significantly increased expansion of the CD4 + or CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…27,29,30 To this end, we decided to investigate the effect of autophagy-ablation in cancer cells undergoing Hyp-PDT elicited ICD on T-cell immunity. Autophagy-competent or autophagy-ablated A375m cancer cells were treated with Hyp-PDT and these were fed to the hu-iDCs for 24 h. Subsequently, these pulsed DCs were exposed to T cells followed by analysis of activation based on their increased proliferation.…”
Section: Autophagy Attenuation In Hyp-pdt Treated Cancer Cells Increamentioning
confidence: 99%
See 1 more Smart Citation
“…Dendritic cells may also offer a powerful vehicle to present modified peptides to the immune system in AML patients [99]. Combination therapies which include chemotherapy to reduce tumor load and immunotherapy to remove MRD are expected to be superseded by conventional therapies used in conjunction with combination-immunotherapy protocols including the vaccination of patients with peptides following adoptive T-cell transfer [100] to remove residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…cancerdiscovery.aacrjournals.org Downloaded from T cells. If one knows the specifi city of these tumor-specifi c T cells, their activity can be further promoted by specifi c synthetic vaccines, again delivered locally, and by low-dose administration of interleukin (IL)-2 or IL-15 (10). Some degree of systemic immunomodulation may still be necessary to create a favorable microenvironment for T-cell entry into tumors that do not naturally allow optimal T-cell access.…”
Section: Selective Activation Of Oxygen-deprivedmentioning
confidence: 99%